Analisis Faktor-Faktor yang Mempengaruhi Perilaku Konsumen Terhadap Keputusan Pembelian Buah di Kota Kendari - Masseleng, Indah Pratiwi; Surni, Surni; Yusria, Wa Ode (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2018)
This study alms to determine a factor affect consumers in the decision to purchase the fruit and the most dominant factor in the decision to buy fruit in Hypermart Lippo Plaza KendariÂ  city and The Fruit Market of Agribisnis Kendari city and fruit most selected by consumers. This research was conducted at Hypermart LippoPlaza Kendari city and The Fruit Market of Agribisnis Kendari city in March to August 2017. The data used in this study consisted of primary data obtained by conducting direct interview on consumers of fruit in Hypermart Lippo Plaza Kendari City and The Fruit Market of Agribisnis Kendari city municipality and secondary data obtained from other written materials related to this research. The analysis used in this research is multiple regression analysis with dummy variable. The results showed that the responses of respondent on product variables, prices, and place no have significant effect on consumer decisions. The dominant variable influenci consumers decision is promotion variable the value of kolerasi between promotion and purchasing decision of fruit is positive. And the fruit of the most selected by respondent is the apple on Hypemart Lippo Plaza Kendari City, while in The Fruit Market of Agribisnis Kendari city is orange